Development of Internal Quality Audit Information System with Personal Extreme Programming (PXP) Approach - Darmansyah Darmansyah; Rifqi Aulia Tanjung; Novita Lizza Anggraini; Vincent Gravie Ebenhaezer Lumenta (Brilliance: Research of Artificial Intelligence, 2024)
Internal Quality Audit (IQA) is an important process to ensure the quality of implementation of activities in educational institutions in accordance with established standards. However, the implementation of IQA that is still carried out manually or semi-digitally can hamper the effectiveness, efficiency, and accuracy in data management and reporting of audit results. Therefore, an information system is needed that can support the audit process in a more systematic and integrated manner. This research examines the development of an internal quality audit system using the Personal Extreme Programming (PXP) approach that is carried out iteratively. The purpose of this study was to evaluate the effectiveness and efficiency of the system developed through four iterations, each of which focused on developing key features such as user management, document management, audit process, and assessment. The PXP methodology was applied to provide flexibility in responding to user feedback, with each iteration resulting in rapid improvements and adjustments according to emerging needs. The results showed that the developed system met the audit management objectives with high functionality, ease of use, and improved efficiency at each iteration. In addition, this iterative approach allows the system to be more responsive to changing user needs compared to conventional development methods. Overall, this research supports the use of PXP as an effective methodology in the development of internal quality audit systems, demonstrating that it can produce solutions that are adaptive, efficient, and suited to user needs.